2001
DOI: 10.1128/jvi.75.15.7059-7066.2001
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray Analysis of Chimpanzee Liver during Acute Resolving Hepatitis C Virus Infection

Abstract: Hepatitis C virus (HCV) poses a worldwide health problem in that the majority of individuals exposed to HCV become chronically infected and are predisposed for developing significant liver disease. DNA microarray technology provides an opportunity to survey transcription modulation in the context of an infectious disease and is a particularly attractive approach in characterizing HCV-host interactions, since the mechanisms underlying viral persistence and disease progression are not understood and are difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
344
3
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 415 publications
(375 citation statements)
references
References 58 publications
22
344
3
6
Order By: Relevance
“…The majority of ISGs identified in our study have also been identified in the experimental chimpanzee model of acute and chronic HCV infection [7][8][9] and in several small studies on human CHC. [22][23][24][25][26][27] Taken together, these studies suggest that the HCV chronically infected liver is capable of mounting an antiviral response.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The majority of ISGs identified in our study have also been identified in the experimental chimpanzee model of acute and chronic HCV infection [7][8][9] and in several small studies on human CHC. [22][23][24][25][26][27] Taken together, these studies suggest that the HCV chronically infected liver is capable of mounting an antiviral response.…”
Section: Discussionmentioning
confidence: 76%
“…Although many different functional groups of genes were identified (results not shown), a significant number (39) were known ISGs (Table 3), indicating an ongoing response to endogenous IFN or the dsRNA response to viral infection. This gene set is remarkably similar to that identified in the HCV experimentally infected chimpanzee [7][8][9] ; however, it represents the most comprehensive list of potential ISGs dif- …”
Section: Isgs Are Upregulated In Chcmentioning
confidence: 78%
See 3 more Smart Citations